2018
DOI: 10.1016/j.compbiomed.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The utility of routine clinical 12-lead ECG in assessing eligibility for subcutaneous implantable cardioverter defibrillator

Abstract: Routine clinical 12-lead ECG can be used to predict S-ICD eligibility. ECG filtering may improve S-ICD eligibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
0
18
1
Order By: Relevance
“…Out-of-sample validation of the lasso and elastic net prediction models in the previous non-ACHD study population 12 yielded high sensitivity of the pre-selected in this study threshold (≥ - 0.5): 100% for the elastic net model, and 77% for lasso model. Validation ROC AUC in a non-ACHD population was unsatisfactory for all models: specifically for lasso (ROC AUC 0.554; 95%CI 0.355-0.754), elastic net (ROC AUC 0.548; 95%CI 0.340-0.756), and ridge model (ROC AUC 0.477; 95%CI 0.282-0.671).…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Out-of-sample validation of the lasso and elastic net prediction models in the previous non-ACHD study population 12 yielded high sensitivity of the pre-selected in this study threshold (≥ - 0.5): 100% for the elastic net model, and 77% for lasso model. Validation ROC AUC in a non-ACHD population was unsatisfactory for all models: specifically for lasso (ROC AUC 0.554; 95%CI 0.355-0.754), elastic net (ROC AUC 0.548; 95%CI 0.340-0.756), and ridge model (ROC AUC 0.477; 95%CI 0.282-0.671).…”
Section: Resultsmentioning
confidence: 73%
“…The results of this study underscore the need to improve S-ICD technology further to increase the number of eligible ACHD patients. Our previous study 12 showed remarkable (3-fold) improvement in S-ICD eligibility after ECG filtering. In this study, high QRS and T voltage was the main reason for S-ICD ineligibility and turning S-ICD ECG filtering feature ON can increase the number of eligible ACHD patients.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations